The ethical price for dairy - Bauer, Katrin (2021)
In the 21st century people in modern society within Europe are used to go to a supermarket to buy groceries of daily need. Everything is easily available and affordable and barely anyone is aware of the production of their consumed goods, their origin and unpleasant side effects. Due to the growing world population, the demand for food is steadily increasing. Among many countries, goods such as meat, fish and dairy have become more attractive and accessible due to low prices and decent income. Access to these products is easy through buying a packaged product at a supermarket. Due to ethical considerations, however, more people decide to omit meat, dairy or eggs and live on a vegetarian or vegan diet. Nevertheless, the majority is still including dairy and eggs in their diet. While it seems rational to live on a vegetarian diet to avoid harm to farm animals as well as their killing for meat, there is comparably little awareness among consumers about the issues arising with dairy industry. In European countries, some specialized cattle breeds, performing well for dairy related traits such as milk yield, calving interval, calving ease and longevity are most commonly used. In order to produce milk, cows need to have a calf approximately once a year. While longevity is emphasized and cows can serve for several years, the consequence is a larger number of offspring than needed for replacement in the dairy industry. Additionally, half of them are bull calves, and therefore of no use for dairy industry. Aforementioned causes several issues concerning the handling of these calves. This starts with the early separation of cow and calf with possible effects on health and behaviour, in addition to the important management of colostrum, followed by the transportation of many calves for enormous routes or the immediate killing of new-born calves due to a lack of economic benefit of raising or selling them. Utilitarianism and abolitionism, two of the most important ethical theories, propose a less cruel livestock industry and suggest to abandon animal-based products to the largest extent possible, recommending a vegetarian or vegan lifestyle. While such a way of taking action might be viable for part of the population, more extensive and adaptable implementations in order to ensure a morally more acceptable animal industry need to be considered. Making use of sexed semen and crossbreeding with beef cattle breeds potentially provides better management practices for dairy farms as well as more profitable calves to enter veal and beef markets. In addition to that, the government and legislation could provide regulations, as for instance carried out in organic dairy industry (see Table 1, p 32.) for extended welfare in the handling of these calves. With respect to these implementations, awareness among consumers needs to be emphasized to achieve the desired shift in dairy industry. Therefore, in this thesis, I aim to review literature on different aspects of dairy industry and will assess some options from a utilitarian and rights-based approach.